A new wild: Reimagining the potential of indigenous biodiversity in Aotearoa, New Zealand. (1st June 2018) - Abbott, Mick; Blackburne, Kate; Boyle, Cameron; Lee, Woody; Pickett, Tenille
This article presents ways to rethink current approaches to protected areas in New Zealand, which have been dominated by problematic colonial ideas that uniformly construct such places as separate from people and as reminiscent of a pre-human past. This has resulted in the strict separation of productive landscapes from protected landscapes in Aotearoa, New Zealand. A re-evaluation of the idea of allocating further lands that have high endemic biodiversity values solely for protection is considered in light of the country's public conservation lands reaching 33 per cent of the country's total land area and still continuing to grow. Using a design-directed research approach we put forward seven alternatives to imagining protected areas that act as speculative futures from which to reimagine and expand the potential of New Zealand's indigenous biodiversity beyond solely preservation-focused approaches that have been based on a fortress conservation model. These futures are not prescriptive but opportunities to extend the value that New Zealand's indigenous biodiversity might have, and consider its capacity to foster deep connections between people and place, in ways in which both endemic biodiversity and people thrive.